Phytochemical Analysis and Anti-Inflammatory Activity of Capparis cartilaginea Decne. from Saudi Arabia: An Ethnopharmacological Study - Alsharif, Bashaer (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2025)
Background: Capparis cartilaginea (C. cartilaginea) is a species belonging to the Capparaceae family, which is known for its various traditional medicinal uses. In Saudi Arabia, the leaves and roots of C. cartilaginea are used in Saudi traditional medicine, primarily as an analgesic for conditions such as osteoarthritis and rheumatoid arthritis and gout, often prepared as an infusion (tea). These traditional applications suggest that C. cartilaginea possesses anti-inflammatory properties. However, the scientific validation of these pharmacological activities remains largely unexplored. Despite several studies investigating the phytochemistry, pharmacology, and safety of various Capparis species, there is a notable gap in research specifically focused on this species. Aim: This study aims to address this gap by systematically investigating the phytochemical constituents of C. cartilaginea, evaluating their anti-inflammatory activities, and understanding their anti-inflammatory mechanisms. Methods: The leaves of C. cartilaginea were used to prepare a traditional infusion (tea). This infusion was then subjected to liquid–liquid partitioning with ethyl acetate and n-butanol. The resulting two organic phases showed similar phytochemical profiles (confirmed by TLC) and were therefore combined into a single organic extract, hereafter referred to as “the extract” throughout the thesis. Both the tea and the extract were analysed for their phytochemical content and tested for anti-inflammatory activity. Phenolic compounds were isolated from the extract and purified using High-Speed Counter Current Chromatography (HSCCC) and size exclusion chromatography. These compounds were then identified using various spectroscopic techniques, including Ultraviolet (UV), Infrared (IR), Mass Spectrometry (MS), and 1D and 2D Nuclear Magnetic Resonance (NMR). Quantification of these compounds in the extract and tea was done by High-Performance Liquid Chromatography (HPLC). The chemical composition of the essential oil extracted from C. cartilaginea was analysed using Gas Chromatography-Mass Spectrometry (GC-MS). A multivariate analysis was conducted to compare the phytochemical constituents of C. cartilaginea with those of other Capparis species, aiding in the chemotaxonomic classification and quality assessment. The anti-inflammatory activity was evaluated using an in vitro model of lipopolysaccharide (LPS)-induced inflammation in murine and human macrophages. This assessment involved analysing inflammatory cytokines, nitric oxide production, matrix metalloproteinases (MMPs), and inflammasome NLRP3 activation through techniques such as enzyme-linked immunosorbent assay (ELISA), Griess assay, gelatine zymography, immunoblotting, and immunofluorescence staining (IF). Results: In addition to gallic acid and adenosine, seven major flavonoids from C. cartilaginea, including kaempferol-3-O-rutinoside (nicotiflorin), quercetin-3-O-rutinoside (rutin), Quercetin 3-(2G-rhamnosylrutinoside) (manghaslin), kaempferol 3-(2G-rhamnosylrutinoside) (clitorin), quercetin-3-O-neohesperidoside (Q-neo), kaempferol-3-O-neohesperidoside (K-neo), and isorhamnetin-3-O-rutinoside (narcissin) were isolated, characterised and quantified in C. cartilaginea extract. These compounds were fully characterised using different spectroscopic techniques. The HPLC analysis specifically quantified the flavonoids, revealing that rutin was the predominant component in the tea and its organic extract, accounting for 264.75 ± 0.17 and 248.75 ± 0.49 μg/g, respectively. The essential oil analysis via GC-MS identified 41 constituents, accounting for 99.99% of the total oil composition. Major compounds included isopropyl isothiocyanate (IPTC) (31.0%), 2- 2-methylbutylnitrile (21.4%), 2-butyl isothiocyanate (18.1%), isobutyronitrile (15.4%), and 3-methylbutylnitrile (8.2%). Multivariate analysis, including principal component analysis (PCA) and agglomerative hierarchical cluster analysis (AHC), revealed that nitrile compounds are prominent and distinctive components of C. cartilaginea essential oil. Their presence, not reported in other Capparis species, suggests that these compounds may serve as reliable chemotaxonomic markers for distinguishing C. cartilaginea from related species. Biological activity assays revealed that C. cartilaginea tea, extracts, and isolated compounds exhibited significant anti-inflammatory activity, with notable reductions in MMP-9, inflammatory cytokines (IL-6, TNF-α, IL-1β), and nitric oxide (NO) production by up to 50-60% in LPS-stimulated macrophages. Inhibition of NLRP3 inflammasome activation was also observed. The essential oil and its main components demonstrated similar anti-inflammatory effects, further validating the traditional use of C. cartilaginea for managing inflammatory conditions. Conclusion: This study has successfully validated the traditional medicinal use of C. cartilaginea for treating inflammatory conditions. Seven flavonoids were identified and quantified in C. cartilaginea extract, and 41 constituents were identified in the essential oil, with isopropyl isothiocyanate emerging as a key chemotaxonomic marker. Biological assays confirmed that C. cartilaginea possess significant anti-inflammatory properties. These findings not only support traditional uses but also provide a scientific basis for potential therapeutic applications. Further in vivo studies and clinical trials are warranted to confirm these effects and explore their clinical relevance.
APPROVED
Keywords: Capparis cartilaginea; Flavonoids; Inflammation; NLRP3